PERANAN SEKTOR PUBLIK DALAM PEREKONOMIAN - SURYADI SURYADI (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
The Role Of The Public Sector In Economy. The government's linkage to improvethe economy of the people is very influential to the community itself, meaning thatthe government can not act if between the government and the people do notsupport each other. Besides, the view of Islam on the role of government in fixingpeople's economy is very much recommended, as happened at the time ofRasulullah SAW.